Perlindungan Hukum Pengguna (Pelanggan) Provider XL Akibat Daur Ulang Nomor Seluler - Sugiarta, Anya Putri; Munandar, Aris (Private Law, 2024)
The purpose of the study is to determine the type of legal protection for users (customers) with the Provider PT. XL Axiata (business actor). This research is normative legal research. The research results show that consumers are disadvantageous to telecommunications service providers (Providers) as businessmen, so users (consumers) can make lawsuits against business actors. Businessmen are also required to provide compensation to consumers unless the provider can prove that the loss was not caused by their fault and/or their negligence. The process of resolving disputes and compensation between providers and customers can be done peacefully but is very difficult to do. Consumers have 2 (two) alternative dispute resolutions, dispute resolution which can be pursued through litigation or non-litigation based on the voluntary choice of the parties to the dispute.